Effect of bioturbation by plateau pika (Ochotona curzoniae) on soil carbon and nitrogen stocks in alpine meadows - Yang Yang; Ruting Hua; Huankun Leng; Jianmin Yao; Jian Yang; Kong Yang (Global Ecology and Conservation)
The plateau pika (Ochotona curzoniae) is a predominant small burrowing herbivore that plays a vital role within the alpine meadow ecosystem of the Qinghai-Tibet Plateau. This investigation centered on delineating the variances in bioturbation impacts by plateau pikas on soil characteristics in alpine meadows under distinct population densities. Outcomes indicated notable discrepancies in SOC, TC, and TN levels between surface soil depth (0–10 cm) and deeper depth (10–20 cm) under different Active Burrow Density (ABD). Across different depths, SOC, TC, and TN concentrations exhibited an initial rise followed by a decline with escalating Active Burrow Density (ABD), reaching peaks within the range of 240–330 burrows per hectare. Additionally, SOC and TN levels displayed synchronized fluctuations across different depths, while TC levels did not exhibit such synchronicity; TC content in deeper depth lagged behind that in surface depth. Moreover, surface soil stoichiometry (C:N ratio) diminished with heightened ABD, whereas deeper depth exhibited an opposing trend. These findings underscore how plateau pika bioturbation reshape nutrient distribution patterns and soil stoichiometry, thereby influencing carbon turnover processes and cycling rates. Drawing upon these findings, the study concludes that moderating plateau pika population density within reasonable thresholds, offers greater promise in stabilizing nutrient cycling processes in alpine meadow and upholding ecological equilibrium.